Tricuspid regurgitation disease stages and treatment outcomes after transcatheter tricuspid valve repair - Schlotter, Florian; Stolz, Lukas; Kresoja, Karl-Patrik; von Stein, Jennifer; Fortmeier, Vera; Koell, Benedikt; Rottbauer, Wolfgang; Kassar, Mohammad; Schöber, Anne; Goebel, Bjoern; Denti, Paolo; Achouh, Paul; et al. (JACC Cardiovascular interventions, 2025)
Background - Tricuspid transcatheter edge-to-edge repair (T-TEER) has emerged as a treatment option for patients with severe tricuspid regurgitation (TR). However, randomized trials have not shown a survival benefit, possibly because of the inclusion of patients in an early or too advanced disease stage. - Objectives - The authors sought to investigate the association between disease stage and outcomes following T-TEER. - Methods - In total, 1,885 patients with significant TR were analyzed, including 585 conservatively treated individuals and 1,300 patients who received T-TEER. Patients were evaluated as part of the prospective EuroTR (European Registry of Transcatheter Repair for Tricuspid Regurgitation) registry and grouped into early, intermediate, and advanced disease stage. Disease stage was based on left and right ventricular function, renal function, and natriuretic peptide levels. The stratification was validated in an external cohort. The primary endpoint was 1-year mortality. - Results - Overall, 395 patients (21% [395/1,885]) were categorized as early, 1,173 patients (62% [1,173/1,885]) as intermediate, and 317 patients (17% [317/1,885]) as advanced disease stage. In patients with early and advanced disease, mortality did not differ between interventional and conservative treatment (early-stage HR: 0.78; 95% CI: 0.34-1.80; P = 0.54; advanced stage HR: 1.06; 95% CI: 0.71-1.60; P = 0.78). However, mortality was significantly lower in patients undergoing percutaneous treatment with intermediate disease stage (HR: 0.73; 95% CI: 0.52-0.99; P = 0.03). - Conclusions - Compared to medically treated controls, T-TEER was associated with 1-year survival at intermediate stage disease but not at early or advanced disease stages. The timing of T-TEER with regard to disease stages might be crucial to optimize treatment benefits.
Online veröffentlicht: 10. Februar 2025
EuroTR Investigators: Philipp M. Doldi, Jürgen Schreieck, Ludwig T. Weckbach, Andreas Goldschmied, Sebastian Rosch, Edoardo Pancaldi, Roman Pfister, Daniela Tomasoni, Stephan Baldus, Natacha Rousse, Muhammed Gerçek, Samy Aghezzaf, Felix Rudolph, Norbert Frey, Sebastian Ludwig, Philip Raake, Christoph Pauschinger, Leonhard-Moritz Schneider, Dominik Felbel, Carsten Salomon, Harald Lapp, Tania Puscas, Alain Berrebi, Amir Abbas Mahabadi, Florian Schindhelm, Berenice Caneiro-Queija, Julio C. Echarte
Gesehen am 09.12.2025